New method for the determination of carbamate and pyrethroid insecticides in water samples using on-line SPE fused core column chromatography - Fernández-Ramos, C; Satínský, D; Solich, P (Talanta, 2014)
A new HPLC column-switching method using large volume sample injection and fused-core columns for on-line solid phase extraction have been developed for the determination of the following carbamates and pyrethroids: aldicarb, carbaryl, pirimicarb, carbofuran, kadethrin, flumethrin, fenpropathrin, fenoxycarb, tau-fluvalinate and fenvalerate, in surface water samples. Sudan I was used as internal standard. The proposed method was performed using 100 µl sample injection followed by an on-line solid phase extraction procedure and finally the compounds were identified and quantified by liquid chromatography with ultraviolet detection. The separation was carried out on C-18 reversed phase column based on fused-core particle technology. The influence of the injected sample volume, the variables affecting to SPE process and the conditions for the separation on an analytical column, were studied and optimized. The limits of detection ranged from 5.5 to 8.9 µg L(-1), and limits of quantification from 18.4 to 29.7 µg L(-1), while inter- and intra-day variability was under 15%. This new analytical procedure was satisfactorily applied for the determination of these organic pollutants in surface water samples located in Czech Republic. Concentration levels were found for some of these pollutants up to 26.11 µg L(-1) in the river Elbe and up to 34.53 µg L(-1) in the closed lakes samples.
Keywords: Organic Chemicals; Solid Phase Extraction; karbamáty; chemické látky znečišťující vodu; Insecticides; jezera; monitorování životního prostředí; Water Pollutants, Chemical; Online Systems; Pyrethrins; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; Rivers; Chromatography, Liquid; spektrofotometrie ultrafialová; Pyrethroids; On-line solid phase extraction (on-line SPE); voda; Surface water; reprodukovatelnost výsledků; Chromatography, High Pressure Liquid; Water; on-line systémy; Large volume sample injection; pyrethriny; Carbamates; Czech Republic; Chromatography; řeky; Spectrophotometry, Ultraviolet; Environmental Monitoring; insekticidy; extrakce na pevné fázi; Česká republika; organické látky; Lakes; chromatografie kapalinová